2016
DOI: 10.1111/1556-4029.13188
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Nocturnal Flight Activity of Blow Flies (Diptera: Calliphoridae) in a Rainforest Fragment in Brazil: Implications for the Colonization of Homicide Victims

Abstract: Nocturnal flight of blow flies (Diptera: Calliphoridae) is a controversial issue in forensic entomology. We performed two field experiments to investigate the diurnal and nocturnal activity of six blow fly species in a rainforest fragment in Brazil. Initially, nocturnal (17:30-05:30) versus diurnal (05:30-17:30) flight activity was investigated. Only 3.9% of adults were collected at night, mostly the native species Mesembrinella bicolor, and nocturnal oviposition did not occur. In the second experiment, collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This is in accordance with Nazni et al [ 38 ], who also demonstrated that C. megacephala exhibited both diurnal and nocturnal activities, but much higher numbers of flies in daytime traps than nighttime traps. Conversely, Sucharit & Tumrasavin [ 20 ] stated an activity peak of C. megacephala at 16:00 to 18:00 h, and no flies during the night, as well as Soares & Vasconcelos [ 39 ], who observed neither nocturnal activity nor oviposition during nighttime. In the present study, minimal numbers of flies were captured during nighttime in summer and rainy season as the sunset was after 18:00 h (nighttime trap was set from 18:00 to 06:00 h), thus flies were still able to be active, entering the traps.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with Nazni et al [ 38 ], who also demonstrated that C. megacephala exhibited both diurnal and nocturnal activities, but much higher numbers of flies in daytime traps than nighttime traps. Conversely, Sucharit & Tumrasavin [ 20 ] stated an activity peak of C. megacephala at 16:00 to 18:00 h, and no flies during the night, as well as Soares & Vasconcelos [ 39 ], who observed neither nocturnal activity nor oviposition during nighttime. In the present study, minimal numbers of flies were captured during nighttime in summer and rainy season as the sunset was after 18:00 h (nighttime trap was set from 18:00 to 06:00 h), thus flies were still able to be active, entering the traps.…”
Section: Discussionmentioning
confidence: 99%